2002
DOI: 10.1093/ajcn/76.5.1048
|View full text |Cite
|
Sign up to set email alerts
|

Home gardens focusing on the production of yellow and dark-green leafy vegetables increase the serum retinol concentrations of 2–5-y-old children in South Africa,,

Abstract: A home-gardening program that was integrated with a primary health care activity, linked to nutrition education, and focused on the production of yellow and dark-green leafy vegetables significantly improved the vitamin A status of 2-5-y-old children in a rural village in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 14 publications
4
106
1
1
Order By: Relevance
“…A home-garden project promoting the cultivation of dark-green leafy vegetables, among others, was conducted in the area from 1998 to 2002. 19 The urban site, which has a low socio-economic level, is situated in the Mariannhill area, Pinetown, approximately 20 km south of the rural site, and is more densely populated.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…A home-garden project promoting the cultivation of dark-green leafy vegetables, among others, was conducted in the area from 1998 to 2002. 19 The urban site, which has a low socio-economic level, is situated in the Mariannhill area, Pinetown, approximately 20 km south of the rural site, and is more densely populated.…”
Section: Study Populationmentioning
confidence: 99%
“…Thirteen percent of the respondents at the rural KZN site said that imifino is good because it contains vitamin A, probably reflecting the effect of a home-garden project that was previously done in the area. 19 Between 20 and 28% of the respondents at the two KZN study sites thought that consumption of imifino saves money (they do not have to buy it because it is freely available). At the rural Limpopo site there clearly is a transfer of knowledge within the households, as mothers and grandmothers were the main source of information on morogo.…”
Section: ;23(1) S Afr J Clin Nutrmentioning
confidence: 99%
See 1 more Smart Citation
“…While consuming a variety of foods is important for meeting essential nutrient requirements needed to promote growth, traditional diets fed to children in developing countries are based predominantly on starchy staples and include few or no nutrient-rich food sources such as animal protein, fruits and vegetables (10)(11)(12) . Often infants and young children are not given the care and attention needed during the selection of nutritious foods and the encouragement needed to eat sufficient amounts of foods (13) .…”
mentioning
confidence: 99%
“…Each of these studies assessed nutritional outcomes as an indicator of changes in food security, and measured them with comparable instruments. Four of the six studies assessed serum retinol concentration as a proxy for smallholders' nutritional status in South Africa (Faber et al 2002), Mozambique (Low et al 2007;Hotz et al 2012b) and Uganda (Hotz et al 2012a); one in Kenya (Hagenimana et al 1999) observed vitamin A intake; and another in Ethiopia (Akalu et al 2010) examined anthropometric measures such as weight-for-age.…”
Section: Effects On Food Securitymentioning
confidence: 99%